Annexure- IV To The Report of the Planning Group on Civil Aviation at the Turn of the Century Working Group IV - Report - Planning Commission (Planning Commission, 1986)
One of the terms of reference of Working Group IV was “to study the productivity and efficiency of various constituent unit of Civil Aviation Sector with a view to recommending suitable norms and measures to improve productivity”. This particular term of reference was also assigned to Working Group - III. It was clarified in the Guidelines given that the Working Group IV would concentrate on the utilisation of aircraft and other equipment available with the Airlines. The matter was further discussed in Planning Group meeting and it was clarified on behalf of Planning Commission that the Working Group IV should concentrate on utilisation of aircraft because this is the fundamental factor which influence the productivity of Airlines operations.
Organisation and Finance
Organisation and Finance